Apocalyptic and integrated views to capitalist universities and academics in Chile - Solari, Enzo (CIAN-Revista de Historia de las Universidades, 2025)
Among those who believe that academic capitalism and the industrialization of universities have developed excessively and uncontrollably in Chile, there is simultaneously and curiously an abandonment of the very need to evaluate these academic-capitalist and market trends. This specific way of elaborating on the theory of academic capitalism follows an empiricist approach, a claim of evaluative neutrality, which makes it necessary to compare it with other robust and contrasting forms of academic capitalism theory that have been designed including explicit evaluative and political elements. Through such a comparison, it is intended to suggest the relationship between the uncritical, almost naturalistic radicalism of the à la chilienne theory and the radicalism with which academic capitalism has developed in Chile, thus highlighting the need to confront the neoliberal influence and the modern technical-economic rationality in the controversial, fragmented, and even declining survival of a certain traditional idea of the university. The different theories of academic capitalism highlight the influence of neoliberal policies and configurations as well as instrumental, technoscientific, and long-standing economic trends. Both aspects should be examined carefully not only comparatively but especially in cases of notable intensity such as the Chilean context, particularly due to its manifestation in the capitalist or industrial mass university and the role the state assumes in relation to it, both as an evaluator and (directly and indirectly) a regulator. This configuration shapes university structures (and experiences), always including a sort of guilty conscience embedded in the same industrial and managerial trends, akin to a challenge to the existing institutions made in the name (like a revival) of what historically has been the essential idea of the university.